Communication Technology: Rebuilding a Better Global Civilization on Earth - Faustinus Sirken (Jurnal Sosial Humaniora, 2023)
The evolution of communication technology fuels ongoing introspectionamong humans, shaping their self-perception and worldview. As reliance onthese tools deepens, individuals delve into their existence and the societalconstructs that govern their lives, potentially steering the development ofcommunication tech for global betterment. Historically, humans havepondered their role as sources of authority and meaning. Liberal perspectivesframe humans as subjective authorities, emphasizing internal experiences toinspire universal meaning. In contrast, Dataists view humans as sources ofauthority and meaning within collective narratives, highlighting therichness of intersubjective experiences among many individuals in oneworld. Utilizing advanced communication technology, notably computeralgorithms, to interpret collective human narratives, this paper suggests apathway for enhancing global civilization. It advocates harnessingtechnology, specifically algorithmic intelligence, to restore a cohesive globalidentity founded on principles of freedom and equality. Employingphenomenological methods, this research examines human experienceswithin the realm of communication technology, drawing on humanism,subjectivism, intersubjectivism, and dataism as theoretical frameworks.